ANALISIS CLOUD KITCHEN DALAM BISNIS F&B: PERAN OPERASIONAL DALAM EFISIENSI BIAYA DAN DAYA SAING DI PERKOTAAN - Avrilyn Vasca Theresian; Nugroho, Christian Rafaele; Evelyn Nethania Haura; Graciella Sherren Kuswandi; Jovan Alvino Pratama; Michael Bryan Ng; Wirjadinata, Patrice; Nurhayati (Integrative Perspectives of Social and Science Journal, 2026)
The rapid growth of digital food delivery platforms has accelerated the emergence of cloud kitchens as an alternative business model in the food and beverage industry. Cloud kitchens operate without dine-in facilities and focus primarily on delivery services through online platforms. This study aims to analyze how operational management contributes to efficiency and competitive advantage in a multi-brand cloud kitchen environment. A qualitative research approach was adopted using an in-depth interview with an operational manager from Hungry Base, a cloud kitchen operator managing multiple food brands within a shared kitchen facility. The findings indicate that operational efficiency is achieved through semi-prepared ingredients supplied from centralized warehouses, standardized operating procedures (SOPs), structured staff training, and shift-based workforce management. Additionally, digital marketing strategies and extended operational hours support the competitiveness of cloud kitchen businesses in highly competitive urban markets. The results highlight that effective integration of supply chain management, operational standardization, and digital promotion strategies plays a critical role in sustaining the cloud kitchen business model.